التدريب وعلاقته بتقييم أداء العاملين - جعفر, حسني (My University, 2019)
his study aims at addressing one of the tools of human resources management. Training is of great importance. It is related to the method of forming and valuing human capital, and on the other hand is one of the basic factors that helps the institution to adapt. Accordingly, In this context, our study is an attempt to demonstrate the effectiveness of the training programs in achieving the objectives of the institution and thus improve the performance by evaluating the latter before and after the training. To achieve this goal, a theoretical study was first carried out. Role And the results of the theoretical section, she stressed that the objectives of the training process are mostly geared to serve the objectives of the institution, and in relation to the results of the questionnaire, It shows the positive role of staff training programs in improving the quality of services provided.
مستغانم DSAمديرية مصالح الفلاحة
Keywords: ادارة موارد بشرية، تدريب ، تقييم الداء ، برامج تدريبية ، معايير تقييم الداء استراتيجيات التدريب